Evaluasi Lingkungan Pengendalian dengan Kerangka Pengendalian Internal COSO di KPP Pratama Jakarta Pesanggrahan - Sekar Puspita Ayu Setiyaviani; Lufti Julian (Politeknik Ganesha Medan, 2023)
The control environment is crucial for establishing a reliable internal control system to prevent corporate fraud at the Jakarta Pesanggrahan Tax Office. It collects state revenue and accesses sensitive taxpayer information, including personal identity and financial data, making it susceptible to fraud risks. This study evaluates the control environment components of the Jakarta Pesanggrahan Tax Office using the 2013 edition of the COSO Internal Control Framework. The study used qualitative descriptive and case study methods. The population of this tax office consists of 93 employees. Primary data was collected through semi-structured interviews with 20 informants from various sections. Secondary data was collected through online sources, regulations, reports, and a literature review. The novelty in this study is that researchers used thematic analysis to produce 37 themes used as indicators in the suitability assessment of control environment components. The research results show that Jakarta Pesanggrahan Tax Office has 31 out of 37 indicators. In the